Thin current sheet behind the dipolarization front - Nakamura,R; Baumjohann,W; Nakamura,TKM; Panov,E; Schmid,D; Varsani,A; Apatenkov,S; Sergeev,VA; Birn,J; Nagai,T; Gabrielse,C; Andre,M; et al. (JGR: Space Physics, 2021)
We report a unique conjugate observation of fast flows and associated current sheet disturbances in the near-Earth magnetotail by MMS (Magnetospheric Multiscale) and Cluster preceding a positive bay onset of a small substorm at ∼14:10 UT, September 8, 2018. MMS and Cluster were located both at X ∼ −14 RE. A dipolarization front (DF) of a localized fast flow was detected by Cluster and MMS, separated in the dawn-dusk direction by ∼4 RE, almost simultaneously. Adiabatic electron acceleration signatures revealed from the comparison of the energy spectra confirm that both spacecraft encounter the same DF. We analyzed the change in the current sheet structure based on multi-scale multi-point data analysis. The current sheet thickened during the passage of DF, yet, temporally thinned subsequently associated with another flow enhancement centered more on the dawnward side of the initial flow. MMS and Cluster observed intense perpendicular and parallel current in the off-equatorial region mainly during this interval of the current sheet thinning. Maximum field-aligned currents both at MMS and Cluster are directed tailward. Detailed analysis of MMS data showed that the intense field-aligned currents consisted of multiple small-scale intense current layers accompanied by enhanced Hall-currents in the dawn-dusk flow-shear region. We suggest that the current sheet thinning is related to the flow bouncing process and/or to the expansion/activation of reconnection. Based on these mesoscale and small-scale multipoint observations, 3D evolution of the flow and current-sheet disturbances was inferred preceding the development of a substorm current wedge.